REVIEW OF THE IMPLEMENTATION OF CLEMENCY IN THE INDONESIAN CRIMINAL LAW SYSTEM: (Study of Constitutional Court Decision Number 32 / PUU-XIV/2016) - Setyaningrum, Putri Imaniar; Setiyono (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2021)
Clemency is a presidential privilege that entails changes, waivers, reductions, or the elimination of criminal executions granted by the President. The scope of clemency is defined in Law No. 5 of 2010, which amends Law No. 22 of 2002 concerning Clemency. The applicable ruling must have a permanent legal force (Inkracht). Clemency can be sought for individuals sentenced to death, life imprisonment, or a minimum sentence of 2 years in prison. This study focuses on the case of Suud Rusli, a death row inmate who unsuccessfully attempted to apply for clemency but was subsequently executed. The research aims to answer the following questions: "What is the procedure for implementing clemency for the death penalty in Indonesia?" and "What is the basis for the Constitutional Court rejecting the Applicant's Application in Decision No. 32/PUU-XIV/2016?" The author uses the Juridical-Normative method, analyzing relevant legal materials, literature, principles, and theories related to the Implementation of Clemency in the Indonesian Criminal Law System (specifically, the Decision of the Constitutional Court No. 32/PUU-XIV/2016). The study reveals significant developments in the submission of clemency for death penalty cases, including a shift from the traditional hanging method under Article 11 of the Penal Code to the usage of Law No. 12/Pnps/1964 on The Procedure of Execution of The Death Penalty Imposed by the Court In the General And Military Court. The Constitutional Court, as one of Indonesia's highest judicial institutions, plays a crucial role in providing a reasoned basis for the consideration of clemency-related matters.